The relationship between private consumption and its driver in Malaysia / Syahrul Akmal Hairul Anuar - Hairul Anuar, Syahrul Akmal (2021)
The study on the relationship between private consumption and its driver in Malaysia is using the yearly data from the year 1980 to 2019. The data used from sources such as World Bank and Department of Statistic. In this study the approach of ordinary least square method was used analyses the drivers of private consumption and to investigate the relationship between the drivers. The finding of this study points that income is the strongest positive relationship to private consumption. There is also other factor that able to explain the private consumption, therefore policy maker can understand the consumption behavior in Malaysia.